The effects of the planning memorandum, time pressure and individual auditor characteristics on audit managers' review time judgments* - BAMBER, E. MICHAEL; BYLINSKI, JOSEPH H. (Contemporary Accounting Research, 1987)
Abstract. This study examines audit managers' review time effort (as reflected in their time estimates for working paper review) and the extent to which this effort is directed by another important audit manager activity: initial audit planning. Initial audit planning is manipulated by identifying certain audit areas as critical in the planning memo. Time pressure and individual auditor characteristics also are examined because auditing literature suggests that they may affect managers' review. The analysis is based on the responses, to an audit case, of 73 audit managers from ten large accounting firms. The results indicate that: 1) the managers exhibit reasonable agreement in budgeting over half of audit management time to review, 2) the initial audit plan directs their subsequent review, 3) time pressure does not significantly affect their estimated review times, and 4) firm affiliation, auditor experience level, and initial planning effort are associated with differences in managers' review practices and perceptions. The paper concludes with a discussion of the implications of these results for practice and further research.